If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -13 + 6x = 7(x + -1) + 2 Reorder the terms: -13 + 6x = 7(-1 + x) + 2 -13 + 6x = (-1 * 7 + x * 7) + 2 -13 + 6x = (-7 + 7x) + 2 Reorder the terms: -13 + 6x = -7 + 2 + 7x Combine like terms: -7 + 2 = -5 -13 + 6x = -5 + 7x Solving -13 + 6x = -5 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -13 + 6x + -7x = -5 + 7x + -7x Combine like terms: 6x + -7x = -1x -13 + -1x = -5 + 7x + -7x Combine like terms: 7x + -7x = 0 -13 + -1x = -5 + 0 -13 + -1x = -5 Add '13' to each side of the equation. -13 + 13 + -1x = -5 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = -5 + 13 -1x = -5 + 13 Combine like terms: -5 + 13 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| x^6-3x^3-4=0 | | ln(3x-14)=2 | | Ix-5I=14 | | -9.12=-2.4y | | -9+5x=5x-9 | | x+6.5=-4.5 | | c-2.59=1.48 | | 3+n^2=2n-9 | | 12y-18*6=4y+3 | | -5-5(2b-7)=7b+13 | | 2*(3(5+2)-1)= | | x^5=550 | | 3+2n=2n-9 | | 2y^2-12y+11=0 | | 30+((4*37)+2)=8+(6*37) | | 3*8+2+1= | | -3r=87 | | 346+45565-4565+-4435= | | 5x-5(-2x+1)=5-2(5x+30) | | 7x-200=5x+4 | | (X-12)=3 | | 2(3x-5)+3(x+2)=5(x+2)-(x+6) | | (5x+10)+58=180 | | H=lw | | 2(3x+5)+3(x+2)=5(x+2)-(x+6) | | 8b+4=4 | | 3x+3y=90 | | 3x-3(2x-8)=2(3x-7)+8x | | 4x-2(3x-8)=2(2x-9)+7x | | 63-=2+3 | | -(-n-8)=40-3n | | w(w-4)=32 |